2023
DOI: 10.1017/hpl.2023.31
|View full text |Cite
|
Sign up to set email alerts
|

Pulse repetition-rate effect on the intensity inside a femtosecond laser filament in air

Abstract: As intense, ultrashort, kHz-repetition-rate laser systems become commercially available, pulse cumulative effects are critical for laser filament based applications. In this work, the pulse repetition rate effect on the femtosecond laser filamentation in air was investigated both numerically and experimentally. The pulse repetition rate effect has negligible influence at the leading edge of filament. Clear intensity enhancement from high repetition pulse is observed at the peak and tailing edge of laser filame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Furthermore, the N 2 and O 2 molecules in excited states or thermal waveguide structures induced by laser pulses may have an impact on the subsequent pulses [12,54], and also on the determination of critical power for self-focusing. The complex dynamics can be revealed through the manipulation of the laser repetition frequency, which requires further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the N 2 and O 2 molecules in excited states or thermal waveguide structures induced by laser pulses may have an impact on the subsequent pulses [12,54], and also on the determination of critical power for self-focusing. The complex dynamics can be revealed through the manipulation of the laser repetition frequency, which requires further studies.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the plasma density and electron temperature inside the filaments in air have been measured and analyzed mostly in the case of air excitation by the femtosecond laser pulses under a single repetition rate [16][17][18] . Recently, laser repetition-related THz production [11] , wake dynamics [19] , fluorescence [20] , clamping intensity [21] , and the cumulative effects [22] from air filaments have been reported as high-energy, ultrashort, high-repetition-rate laser systems become commercially accessible. Through pump-probe experiments [23] , we recently found that the low-density region, due to the accumulative effect by 1 kHz repetition filaments, results in higher plasma density obtained in the measurements.…”
Section: Introductionmentioning
confidence: 99%